Gender As a Moderator in Relation Between Self-Esteem and Social Media Activity Based on Instagram Platform - Emilian GWIAZDZINSKI (Communications of International Proceedings, 2022)
The current times are called the times of digital communication, where social media such as Facebook, Instagram and Tik Tok are the main means of communication. Communities, apart from communication by itself, spend time viewing content and its creation usually in the form of graphics or videos. On this basis, the purpose of the study was to identify whether a variable such as the level of self-esteem demonstrates a relationship with social media activity and whether the gender of a given representative of such a community is a moderator of this relationship. From the study conducted on a sample of 272 individuals, it emerged that the relationship between self-esteem and social media activity is negative, with high levels of self-esteem being accompanied by low social media activity, while low levels of self-esteem are accompanied by high social media activity. It also appeared that gender moderates the relationship studied and, in the case of women, high social media activity occurs with low self-esteem and, as self-esteem increases, social media activity decreases. In the case of men, no such effect was observed.
Keywords: self-esteem; gender; activity on social media; activity on the Instagram platform